RFID-Based Tourism Information System - Abdul Hamid, Nurul Hannah (Universiti Teknologi PETRONAS, 2009)
The purpose of this dissertation is to record all relevant activities involving research which focuses on developing tourist information system via Radio Frequency Identification (RFID). The RFID system aims to provide an alternative and automate the current method of conveying information to the tourist who came to Malaysia. Currently, the current method to convey information to the tourist is through brochures, maps, the internet, tourist information counter, etc. Personalization is tailoring to a user based on personal detail or characteristic they provide. If the tourist or user is Malaysian, the information display will be in Bahasa Malaysia, and if the tourist is from France, the information will be display in French language. The personalization is based on the language used by the tourists and their nationality. Personalization provides better information as it provides more specific information that is increasingly relevant to a person's interest and increase the reliability of information. It is usually in accordance with individuals' standards, tastes and preferences. The methodology adopted is prototyping-based methodology. In addition, the technology used for the project development is purely RFID using passive RFID tag and passive RFID fixed reader. Based on the author's research, the RFID technology is suitable to be used for this particular system. It is hope that the RFID based Tourist Information System can be used as a tool to convey information, displaying welcome messages, routes or promotions to the Malaysian tourists in the future. This dissertation also includes introduction, project literature review and study, project work and methodology, result and discussion, conclusion and recommendations and last but not least, references and appendices. -